Efforts to Increase Physical and Social Immunity in Adolescents: A Study of Cardiorespiratory Endurance in Adolescents through Jumping Rope and Deep Walking Activities - Herdianty Kusuma Handari; Mei Kusumaningtyas (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Adolescents today experience a decline in fitness, even though fitness is related to health. To improve fitness, there are many choices of sports or simple exercises that can be done, including jumping rope and brisk walking. These two exercises will be compared to find out which exercise is better in increasing cardiorespiratory endurance in adolescents. This study was an experimental study with a randomized control trial design on a total of 51 subjects divided into three groups, namely the jumping rope group (15 subjects), the brisk walking group (17 subjects) and the control group (19 subjects). The jump rope exercise was performed for 15 minutes, twice a day, while the brisk walking exercise was performed for 30 minutes. Both were carried out for 12 times, while the control group was not given any treatment. The results of the statistical analysis of the pre-test and post-test using Wilcoxon showed a value of p=0.050 in the jumping rope group, p=0.001 in the brisk walking group, and p=0.080 in the control group, while the post-test using Mann Whitney between the jumping rope and brisk walking shows the value of p=0.766. Jump rope and brisk walking can both increase cardiorespiratory endurance, but neither is better.